Impact of Scabies on Sleep Quality - Azzahra, Fatimah; Manuputty, Amanda Gracia; Bandjar, Fitri Kadarsih; Silalahi, Parningotan Yosi (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Scabies is an infectious skin condition that occurs due to an infestation of the small parasitic mite known as Sarcoptes scabiei var. hominis. It causes symptoms of itching, which usually worsen during the night and can interfere with sleep. Purpose: The aim of the study was to examine how the incidence of scabies relates to the sleep quality of students at Al Anshor Islamic Boarding School in 2022. Methods: In this study, a quantitative approach was used with a cross-sectional research design. Primary data was collected through the diagnosis of scabies and the use of the Pittsburgh Sleep Quality Index (PSQI) questionnaire to measure sleep quality. Bivariate analysis was conducted using the chi-square test for data analysis. The research sample was obtained through the stratified random sampling method. Results: According to the findings, out of 42 participants, 26 students (61.9%) had scabies, with 11 males and 15 females affected. Most of the scabies cases were found in 17-year-old students. The study also found that all scabies sufferers had poor quality sleep. Statistical analysis revealed a significant association between the incidence of scabies and sleep quality, with a p-value of 0.000 and a 95% confidence interval. Conclusion: In conclusion, the study suggests that there is a link between the occurrence of scabies and sleep quality. Therefore, it is important to raise awareness about personal hygiene practices to reduce the spread of scabies.